ALFREDO GOMES DE FARIA JÚNIOR AND THE BRAZILIAN PHYSICAL EDUCATION IN THE YEARS 1960 AND 1970: A HISTORY THAT IS COUNTED (Fiep Bulletin - online, 2014)
The present study intends to narrate, through the history of the teacher`s Alfredo Gomes Faria Júnior's   life, one of the possible histories of the Brazilian physical education in the years 1960 and 1970. The life path is configured as one of the access keys to the understanding of the dynamics of the academic and professional field of the physical education in that period. The Faria Júnior's life, from your childhood until the professional formation and your subsequent exercise, indicates as the socialization of the biographed with different institutions (club, Military School of Rio de Janeiro, National School of physical education and Sports, sporting institutions and the teaching) they formed values and dispositions that influenced your professional performance excessively. Such devices and values were at that time present in the physical education professional's habit. This way, your path helps to explain the transformations and ambiguities that were operated in the habit that conformed the field of the physical education. On the other hand, we have in your path the possibility to relative the hypothesis, built by the critics in the years 1980, that the period in subject had the sporting model of high revenue as pedagogic model transplanted for the teaching of the school physical education. Faria Júnior's experience as teacher in schools of first and second degrees and as author of the book "Didacticism of Physical Education" (1969) indicates that the values, means and ends of the sport of high revenue were resigned and systematized in way they be adapted to the values, means and ends of the school.
Keywords: History; History of Life; School Physical Education